Kinerja Belanja Daerah Pemerintah Provinsi DKI Jakarta - Ferica Christinawati Putri (CV. Multi Kreasi Media, 2023)
Budget Realization Reports (LRA) published by regional governments as a form of regional government accountability in providing information that is very useful for users of regional financial information to assess regional financial performance. LRA is one of the main regional financial accountability reports. Regional spending reflects local government policies and the direction of regional development. The object of research is the Provincial Government of DKI Jakarta. The aim of the study was to analyze the performance of regional spending based on the ratio of growth and compatibility in the Budget Realization Report (LRA) for the Provincial Government of DKI Jakarta for the 2020-2021 fiscal year. The analytical method used is descriptive analysis method which is carried out by making a description of the problems that have been identified. From the results of the analysis which consists of analysis using growth and compatibility ratios, it shows that there is positive growth in the performance of regional expenditures and the orientation of the expenditure performance of the DKI Jakarta Provincial Government on operational activities of 86.41% compared to capital expenditure activities of 8.67%.